Effects of gold and PCL- or PLLA-coated silica nanoparticles on brain endothelial cells and the blood–brain barrier - Bittner, Aniela; Ducray, Angélique D.; Widmer, Hans Rudolf; Stoffel, Michael H.; Mevissen, Meike (Beilstein Journal of Nanotechnology, 2019)
Nanomedicine is a constantly expanding field, facilitating and improving diagnosis and treatment of diseases. As nanomaterials are foreign objects, careful evaluation of their toxicological and functional aspects prior to medical application is imperative. In this study, we aimed to determine the effects of gold and polymer-coated silica nanoparticles used in laser tissue soldering on brain endothelial cells and the blood–brain barrier using rat brain capillary endothelial cells (rBCEC4). All types of nanoparticles were taken up time-dependently by the rBCEC4 cells, albeit to a different extent, causing a time- and concentration-dependent decrease in cell viability. Nanoparticle exposure did not change cell proliferation, differentiation, nor did it induce inflammation. rBCEC4 cells showed blood–brain barrier characteristics including tight junctions. None of the nanoparticles altered the expression of tight junctions or impaired the blood–brain barrier permeability. The findings suggest that effects of these nanoparticles on the metabolic state of cells have to be further characterized before use for medical purposes.
Keywords: blood–brain barrier; laser tissue soldering; nanomedicine; nanoparticle uptake; rBCEC4 cells

(untitled) - Vance, M. E.; Kuiken, T.; Vejerano, E. P.; McGinnis, S. P.; Hochella, M. F., Jr; Rejeski, D.; Hull, M. S. (Beilstein J. Nanotechnol., 2015)

(untitled) - Raffa, V.; Vittorio, O.; Riggio, C.; Cuschieri, A. (Minimally Invasive Ther. Allied Technol., 2010)

(untitled) - Puca, A.; Albanese, A.; Esposito, G.; Maira, G.; Tirpakova, B.; Rossi, G.; Mannocci, A.; Pini, R. (Neurosurgery, 2006)

(untitled) - Leclère, F. M.; Schoofs, M.; Buys, B.; Mordon, S. R. (Plast. Reconstr. Surg., 2010)

(untitled) - Bogni, S.; Ortner, M.-A.; Vajtai, I.; Jost, C.; Reinert, M.; Dallemagne, B.; Frenz, M. (Gastrointest. Endoscopy, 2012)

(untitled) - Schöni, D. S.; Bogni, S.; Bregy, A.; Wirth, A.; Raabe, A.; Vajtai, I.; Pieles, U.; Reinert, M.; Frenz, M. (Lasers Surg. Med., 2011)

(untitled) - Matteini, P.; Ratto, F.; Rossi, F.; Pini, R. (Quantum Electron., 2014)

(untitled) - Esposito, G.; Rossi, F.; Matteini, P.; Scerrati, A.; Puca, A.; Albanese, A.; Rossi, G.; Ratto, F.; Maira, G.; Pini, R. (Lasers Surg. Med., 2013)

(untitled) - Ducray, A. D.; Stojiljkovic, A.; Möller, A.; Stoffel, M. H.; Widmer, H.-R.; Frenz, M.; Mevissen, M. (Nanomedicine (N. Y., NY, U. S.), 2017)

(untitled) - Zielinski, J.; Möller, A.-M.; Frenz, M.; Mevissen, M. (Nanomedicine (N. Y., NY, U. S.), 2016)

(untitled) - Koch, F.; Möller, A.-M.; Frenz, M.; Pieles, U.; Kuehni-Boghenbor, K.; Mevissen, M. (Toxicol. In Vitro, 2014)

(untitled) - Kamikubo, Y.; Yamana, T.; Hashimoto, Y.; Sakurai, T. (ACS Chem. Neurosci., 2019)

(untitled) - Wu, J.; Wang, C.; Sun, J.; Xue, Y. (ACS Nano, 2011)

(untitled) - Patabendige, A.; Skinner, R. A.; Morgan, L.; Joan Abbott, N. (Brain Res., 2013)

(untitled) - Engelhardt, B.; Liebner, S. (Cell Tissue Res., 2014)

(untitled) - Erickson, M. A.; Banks, W. A. (J. Cereb. Blood Flow Metab., 2013)

(untitled) - Simko, M.; Mattsson, M.-O. (Curr. Med. Chem., 2014)

(untitled) - Baghirov, H.; Karaman, D.; Viitala, T.; Duchanoy, A.; Lou, Y.-R.; Mamaeva, V.; Pryazhnikov, E.; Khiroug, L.; de Lange Davies, C.; Sahlgren, C.; Rosenholm, J. M. (PLoS One, 2016)

(untitled) - Trickler, W. J.; Lantz, S. M.; Murdock, R. C.; Schrand, A. M.; Robinson, B. L.; Newport, G. D.; Schlager, J. J.; Oldenburg, S. J.; Paule, M. G.; Slikker, W., Jr; Hussain, S. M.; Ali, S. F. (Nanotoxicology, 2011)

(untitled) - Trickler, W. J.; Lantz-McPeak, S. M.; Robinson, B. L.; Paule, M. G.; Slikker, W., Jr; Biris, A. S.; Schlager, J. J.; Hussain, S. M.; Kanungo, J.; Gonzalez, C.; Ali, S. F. (Drug Metab. Rev., 2014)

(untitled) - Guo, C.; Xia, Y.; Niu, P.; Jiang, L.; Duan, J.; Yu, Y.; Zhou, X.; Li, Y.; Sun, Z. (Int. J. Nanomed., 2015)

(untitled) - Schulze-Osthoff, K.; Ferrari, D.; Riehemann, K.; Wesselborg, S. (Immunobiology, 1997)

(untitled) - Liu, X.; Sui, B.; Sun, J. (Biomaterials, 2017)

(untitled) - Freese, C.; Anspach, L.; Deller, R. C.; Richards, S.-J.; Gibson, M. I.; Kirkpatrick, C. J.; Unger, R. E. (Biomater. Sci., 2017)

(untitled) - Matteini, P.; Ratto, F.; Rossi, F.; Rossi, G.; Esposito, G.; Puca, A.; Albanese, A.; Maira, G.; Pini, R. (J. Biomed. Opt., 2010)

(untitled) - Polakis, P. (J. Cell Biol., 2008)

(untitled) - Grossen, P.; Québatte, G.; Witzigmann, D.; Prescianotto-Baschong, C.; Dieu, L.-H.; Huwyler, J. (J. Nanomater., 2016)

(untitled) - Lin, H.; Yue, Y.; Maidana, D. E.; Bouzika, P.; Atik, A.; Matsumoto, H.; Miller, J. W.; Vavvas, D. G. (Semin. Ophthalmol., 2016)

(untitled) - Saraiva, C.; Praça, C.; Ferreira, R.; Santos, T.; Ferreira, L.; Bernardino, L. (J. Controlled Release, 2016)

(untitled) - Zhou, Y.; Peng, Z.; Seven, E. S.; Leblanc, R. M. (J. Controlled Release, 2018)

(untitled) - Barillet, S.; Simon-Deckers, A.; Herlin-Boime, N.; Mayne-L’Hermite, M.; Reynaud, C.; Cassio, D.; Gouget, B.; Carrière, M. (J. Nanopart. Res., 2010)

Advances in Molecular Toxicology - Petushkov, A.; Ndiege, N.; Salem, A. K.; Larsen, S. C. (Toxicity of Silica Nanomaterials: Zeolites, Mesoporous Silica, and Amorphous Silica Nanoparticles, 2010)

(untitled) - Klingberg, H.; B. Oddershede, L.; Loeschner, K.; Larsen, E. H.; Loft, S.; Møller, P. (Toxicol. Res. (Cambridge, U. K.), 2015)

(untitled) - Fujioka, K.; Hanada, S.; Inoue, Y.; Sato, K.; Hirakuri, K.; Shiraishi, K.; Kanaya, F.; Ikeda, K.; Usui, R.; Yamamoto, K.; Kim, S.; Manome, Y. (Int. J. Mol. Sci., 2014)

(untitled) - Manning, B. D.; Toker, A. (Cell, 2017)

(untitled) - Han, S. G.; Newsome, B.; Hennig, B. (Toxicology, 2013)

Assay Guidance Manual - Riss, T. L.; Moravec, R. A.; Niles, A. L.; Duellman, S.; Benink, H. A.; Worzella, T. J. (Cell Viability Assays, 2004)

Nanoparticulate Drug Delivery - Patravale, V.; Dandekar, P.; Jain, R. (Nanotoxicology: evaluating toxicity potential of drug-nanoparticles, 2012)

(untitled) - Kuo, Y.-C.; Tsai, H.-C. (Mater. Sci. Eng., C, 2018)

(untitled) - Ragnaill, M. N.; Brown, M.; Ye, D.; Bramini, M.; Callanan, S.; Lynch, I.; Dawson, K. A. (Eur. J. Pharm. Biopharm., 2011)

(untitled) - Roux, F.; Couraud, P.-O. (Cell. Mol. Neurobiol., 2005)

(untitled) - He, Y.; Yao, Y.; Tsirka, S. E.; Cao, Y. (Stroke, 2014)

(untitled) - Helms, H. C.; Abbott, N. J.; Burek, M.; Cecchelli, R.; Couraud, P.-O.; Deli, M. A.; Förster, C.; Galla, H. J.; Romero, I. A.; Shusta, E. V.; Stebbins, M. J.; Vandenhaute, E.; et al. (J. Cereb. Blood Flow Metab., 2016)

(untitled) - Blasig, I. E.; Giese, H.; Schroeter, M. L.; Sporbert, A.; Utepbergenov, D. I.; Buchwalow, I. B.; Neubert, K.; Schönfelder, G.; Freyer, D.; Schimke, I.; Siems, W.-E.; Paul, M.; et al. (Microvasc. Res., 2001)

(untitled) - Schönbächler, A.; Glaied, O.; Huwyler, J.; Frenz, M.; Pieles, U. (J. Photochem. Photobiol., A, 2013)

(untitled) - Stojiljković, A.; Kuehni-Boghenbor, K.; Gaschen, V.; Schüpbach, G.; Mevissen, M.; Kinnear, C.; Möller, A.-M.; Stoffel, M. H. (Nanoscale, 2016)

(untitled) - Srinivasan, B.; Kolli, A. R.; Esch, M. B.; Abaci, H. E.; Shuler, M. L.; Hickman, J. J. (J. Lab. Autom., 2015)

(untitled) - Cecchelli, R.; Aday, S.; Sevin, E.; Almeida, C.; Culot, M.; Dehouck, L.; Coisne, C.; Engelhardt, B.; Dehouck, M.-P.; Ferreira, L. (PLoS One, 2014)